(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
In the article the current situation and development issues of the tourism industry in the province of Tehran are given based on the analysis and generalization of factual material and statistical data of basic infrastructures, such as hotel service, air transport, vehicles, guides՛ institute and catering services.